Preliminary results of a labor productivity problem in the quotation department of a small growing co-packing company - Gonzalez Silva, Julio Cesar; Roldán Nariño, Raúl Fabián; Flórez Rubio, Luis Hernando (Documentos de Trabajo ECBTI, 2020)
Abstract: Colombia, like other Latin American countries, is a country of small and medium-sized enterprises (SMEs), where the use of operational (unskilled) labor is intensive, under a configuration of cells and/or process lines for manufacturing or providing services of different kinds. This article is based on a review of the case of a company that stands out in the market as a provider of contract packing services and support for logistics processes in the city of Medellín (Colombia); it presents difficulties in its growth and capacity to respond to customers. The process of quotations appears as a bottleneck of all its commercial and operative work, product of a formal design, based on rigorous calculations of normal times and complex standards that require qualified human resources and a time of elaboration that affects costs and time of response. This is the first review and conclusions of the analysis made to the process under study.